Adenocarcinoma in situ admixed with small cell neuroendocrine carcinoma of the cervix: A case report with cytological features. Issue 9 (15th April 2018) - Nishiumi, Yukimi; Nishimura, Toshiyuki; Kashu, Ippei; Aoki, Takayuki; Itoh, Ryoji; Tsuta, Koji; Ishida, Mitsuaki
Abstract : Primary cervical small cell neuroendocrine carcinoma (SCNEC) is a rare and aggressive tumor. Herein, we describe the first cytological case of adenocarcinoma in situ (AIS) admixed with SCNEC. A 65‐year‐old postmenopausal Japanese female presented with abnormal genital bleeding. The Papanicolaou smear of the cervix demonstrated the presence of 2 distinct neoplastic components in an inflammatory background. One component consisted of aggregates of small round cells with a high nuclear/cytoplasmic ratio and round to oval nuclei with powdery chromatin, and inconspicuous nucleoli. Nuclear molding was characteristic. The other component consisted of irregular overlapping clusters of tall columnar cells with large round to oval nuclei containing coarse chromatin, and relatively rich cytoplasm. Accordingly, AIS admixed with SCNEC was suspected. Although the cytological features of cervical SCNEC are characteristic, the cytodiagnosis of this type of tumor may be difficult because of the rarity of the tumor. The presence of non‐neuroendocrine tumor components in cervical SCNEC is not unusual, therefore careful observation is needed not to miss SCNEC components in the diagnosis of squamous cell carcinoma and/or adenocarcinoma in cervical cytological specimens.